Parametric study of seed‐layer formation for low‐temperature hydrothermal growth of highly oriented ZnO films on glass substrates. Issue 6 (21st February 2013) - Podlogar, Matejka; Vengust, Damjan; Richardson, Jacob J.; Strojnik, Martin; Mazaj, Matjaž; Trefalt, Gregor; Daneu, Nina; Rečnik, Aleksander; Bernik, Slavko
Abstract Applications involving transparent conducting films (TCFs), such as flat‐panel displays and touch screens technologies, are dominated by indium‐tin‐oxide (ITO). Increasing prices of indium in hand with weaknesses of ITO films make a strong argument for alternative TCFs with competitive characteristics and lower price. Here we demonstrate the potential of highly oriented zinc oxide (ZnO) films grown on glass substrates under low‐temperature hydrothermal (HT) conditions at 90 °C from aqueous solutions of Zn‐nitrate and Na‐citrate. Formation of a continuous ZnO seed‐layer with proper thickness, grain size, connectivity, and orientation of seed‐grains on glass is shown to be essential to achieve conditions for the growth of highly oriented (0001), smooth, transparent, and conductive ZnO films according to the spatially confined oriented growth (SCOG) mechanism. The film grown on homogeneous seed‐layer with grain size of about 20 nm showed optical transmittance of up to 82% and relatively low resistivity for undoped ZnO ceramic in order of few 100 Ω sq−1. Such characteristics are explained by highly oriented crystalline texture and high coalescence of ZnO crystals in these films.